2w=7w-60

Simple and best practice solution for 2w=7w-60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2w=7w-60 equation:



2w=7w-60
We move all terms to the left:
2w-(7w-60)=0
We get rid of parentheses
2w-7w+60=0
We add all the numbers together, and all the variables
-5w+60=0
We move all terms containing w to the left, all other terms to the right
-5w=-60
w=-60/-5
w=+12

See similar equations:

| 9(p−87)=45 | | 9(j−87)=45 | | 0.25m=8 | | 6x-20=3x+45} | | 5^2x^-4-1=0 | | 4y-4y=-6 | | -10k+6k=-40 | | 4(w)=168 | | 2(3w)+2(w)=168 | | 2(3w)+(w)=168 | | 2k-3-7-7=8k-5 | | 3c-12=8c-94 | | 3^(2x)+3^3=106 | | 3^2x+3^3=106 | | 7k-3=1+6k | | (2x+15)+(6x-37)/2=3x+5 | | 4t–76°=4t | | -3+2n=n+5 | | 11m-7=4m-28 | | 2x-14=8x+22 | | 4(1+7k)-7=-3(1+2k) | | 25y+5=23y-7 | | 27y+7=25y+5 | | -4(2x+1)=-4(-5+x) | | 5m-7=-(m+5)-5 | | 6n–7n–=4+n | | 3(-6-5x)=-3-3(3x+1) | | 3(-6-5x)=-3-3(3x+1 | | 4x+3=7;x= | | 3x+-5=2x+1 | | X+7=-x+10 | | -8b-8(4b-3)=-6(6b+4) |

Equations solver categories